Adaptation and Assessment of Reliability and Validity of the Greek Version of the Ohkuma Questionnaire for Dysphagia Screening - Papadopoulou, Soultana L.; Exarchakos, Georgios; Christodoulou, Dimitrios; Theodorou, Stavroula; Beris, Alexandre; Ploumis, Avraam (International Archives of Otorhinolaryngology, 2017)
Introduction The Ohkuma questionnaire is a validated screening tool originally used to detect dysphagia among patients hospitalized in Japanese nursing facilities.Objective The purpose of this study is to evaluate the reliability and validity of the adapted Greek version of the Ohkuma questionnaire.Methods Following the steps for cross-cultural adaptation, we delivered the validated Ohkuma questionnaire to 70 patients (53 men, 17 women) who were either suffering from dysphagia or not. All of them completed the questionnaire a second time within a month. For all of them, we performed a bedside and VFSS study of dysphagia and asked participants to undergo a second VFSS screening, with the exception of nine individuals. Statistical analysis included measurement of internal consistency with Cronbach's α coefficient, reliability with Cohen's Kappa, Pearson's correlation coefficient and construct validity with categorical components, and One-Way Anova test.Results According to Cronbach's α coefficient (0.976) for total score, there was high internal consistency for the Ohkuma Dysphagia questionnaire. Test-retest reliability (Cohen's Kappa) ranged from 0.586 to 1.00, exhibiting acceptable stability. We also estimated the Pearson's correlation coefficient for the test-retest total score, which reached high levels (0.952; p = 0.000). The One-Way Anova test in the two measurement times showed statistically significant correlation in both measurements (p = 0.02 and p = 0.016).Conclusion The adapted Greek version of the questionnaire is valid and reliable and can be used for the screening of dysphagia in the Greek-speaking patients.
Keywords: questionnaire; prevalence; deglutition; deglutition disorders